2022
DOI: 10.1111/pce.14430
|View full text |Cite
|
Sign up to set email alerts
|

Early or late? The role of genotype phenology in determining wheat response to drought under future high atmospheric CO2 levels

Abstract: The combination of a future rise in atmospheric carbon dioxide concentration ([CO2]) and drought will significantly impact wheat production and quality. Genotype phenology is likely to play an essential role in such an effect. Yet, its response to elevated [CO2] and drought has not been studied before. Here we conducted a temperature‐controlled glasshouse [CO2] enrichment experiment in which two wheat cultivars with differing maturity timings and life cycle lengths were grown under ambient (aCO2 approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…For example, to account for [CO₂] effects, RUE and TE are adjusted through linear or near‐linear functions (O'Leary et al, 2015). Several studies, however, have shown a complex genotype‐by‐environment interaction under elevated [CO 2 ] (eCO 2 ) and different meteorological conditions that challenge the notion of a simple adjustment of these parameters through a linear function of [CO₂] (Eller et al, 2020; Jiang et al, 2022). Thus, a more robust model representation of such important parameters is required to account for observed climate and [CO 2 ] effects on crops.…”
Section: Introductionmentioning
confidence: 99%
“…For example, to account for [CO₂] effects, RUE and TE are adjusted through linear or near‐linear functions (O'Leary et al, 2015). Several studies, however, have shown a complex genotype‐by‐environment interaction under elevated [CO 2 ] (eCO 2 ) and different meteorological conditions that challenge the notion of a simple adjustment of these parameters through a linear function of [CO₂] (Eller et al, 2020; Jiang et al, 2022). Thus, a more robust model representation of such important parameters is required to account for observed climate and [CO 2 ] effects on crops.…”
Section: Introductionmentioning
confidence: 99%